Sams in Gefahr - Maar, Paul (Oetinger, 2002)
The Sams, a clever and unusual creature, helps Herr Taschenbier and young Martin Taschenbier gain self-confidence and grants their wishes. Martin and his friends Tina and Roland must save the Sams from danger.
Keywords: Kinderbuch; Self-confidence; Wishes; Rettung; Erfüllung; Humor; Krankheit; Lehrer; Fabeltiere; Magie; Wirklichkeit; Wunsch